Development of Multifunctional Histone Deacetylase 6 Degraders with Potent Antimyeloma Activity - Wu, Hao; Yang, Ka; Zhang, Zhongrui; Leisten, Eric D; Li, Ziyuan; Xie, Haibo; Liu, Jin; Smith, Kerry A; Novakova, Zora; Barinka, Cyril; Tang, Weiping (Journal of medicinal chemistry, 2019)
Histone deacetylase 6 (HDAC6) primarily catalyzes the removal of acetyl group from the side chain of acetylated lysine residues in cytoplasmic proteins such as α-tubulin and HSP90. HDAC6 is involved in multiple disease-relevant pathways. Based on the proteolysis targeting chimera strategy, we previously developed the first HDAC6 degrader by tethering a pan-HDAC inhibitor with cereblon (CRBN) E3 ubiquitin ligase ligand. We herein report our new generation of multifunctional HDAC6 degraders by tethering selective HDAC6 inhibitor Nexturastat A with CRBN ligand that can synergize with HDAC6 degradation for the antiproliferation of multiple myeloma (MM). This new class of degraders exhibited improved potency and selectivity for the degradation of HDAC6. After the optimization of the linker length and linking positions, we discovered potent HDAC6 degraders with nanomolar DC50 and promising antiproliferation activity in multiple myeloma (MM) cells.
Keywords: HeLa Cells; proliferace buněk; Hep G2 Cells; vztah mezi dávkou a účinkem léčiva; buňky Hep G2; Histone Deacetylase 6; Drug Development; inhibitory histondeacetylas; MFC-7 buňky; vyvíjení léků; lidé; HeLa buňky; Antineoplastic Agents; MCF-7 Cells; protinádorové látky; mnohočetný myelom; Histone Deacetylase Inhibitors; Dose-Response Relationship, Drug; Cell Proliferation; Multiple Myeloma; histondeacetylasa 6; Humans